Pengaruh Price, Service Quality Dan Marketing Online Terhadap Keputusan Pembelian (Pada Toko Sepatu Ghealsy Malang) - Siti Nur Waidah; Muhammad Ridwan Basalama; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine the effect of price, service quality and online marketing on purchasing decisions. While the independent variables used in this study are price, service quality and online marketing and the dependent variable is purchasing decisions. The sample used in this study was a simple random sampling technique consisting of 86 respondents. Then the research data was processed using instrument tests, classical assumptions, multiple linear regression, and hypothesis testing, namely f-test and t-test.The results of this study indicate that price, service quality and online marketing have an effect on purchasing decisions at Gealsy Malang shoe stores. Keywords: Price, service quality, online marketing, and purchasing decisions